Territorial Edge Computing Enabling Green Tourism and Green Development of CIPP Model Analytics - Bian, Yuqi (EAI Endorsed Transactions on Energy Web, 2023)
INTRODUCTION: Eco-development is an essential national strategy, which has become an effective way to sustain China’s tourism industry in the new era. Nowadays, the problem of climate change is becoming more and more serious, and the restriction on natural resources and the environment is becoming more and more serious. Improving the economic efficiency of the tourism industry and advancing the reform of its economic efficiency are critical priorities for the high-quality development of the tourism industry. Therefore, it is crucial for edge computing to empower green tourism and green growth. OBJECTIVES: The purpose is to enhance the development of green tourism in China and promote the sustainable development of China’s tourism industry; to solve the problems of severe environmental damage and resource consumption in the development of the tourism industry; and to promote the application of information technology, such as full-area edge computing, in the development of China’s tourism industry, and to realize the combination of the CIPP education concept and the concept of green tourism promotion. METHODS:Firstly, the authors find the necessity of researching the CIPP model of green tourism and green development empowered by the whole domain edge computing by using the study of literature and theory; secondly, the Author analyzes the importance of the education of the concept of green tourism and green development by using the method of analyzing the CIPP model; and lastly, the authors measure and enhance the effectiveness of green tourism and green development by using the mobile whole domain edge computing. RESULTS: The whole-domain edge computing has better stability for green tourism and green development measurement, and the use of the CIPP model can better deepen tourists’ tourism concepts of green tourism and green development and promote green tourism development. CONCLUSION: The level of innovation in China’s tourism industry is improving, and multivariate analysis shows that innovation is the key force driving industrial change and quality development. Therefore, it is essential to continue supporting an innovative and technology-driven tourism industry and continuously improving its innovative technologies and content. Greater emphasis will be placed on training and improving the quality of tourism staff. Tourism talent is the basis for innovation in tourism management and services and a critical factor in the development of an innovative system for tourism.